Assessment of hemodialysis efficiency in children suffering end stage renal disease using serum cystatin - C Levels - Mohamed Mohamed Abdelhamied Soliman; Abbass Abdelfattah Mourad; Fatina Ibrahim Fadel; Hafez Mahmoud Bazaraa (Cairo : Mohamed Mohamed Abdelhamied Soliman, 2014)
The goals of pediatric hemodialysis (HD) include removal of excess fluid in addition to effective and safe solute clearance which includes not only small plasma solutes, but also middle molecules and protein-bound solutes. Three general types of dialyzers are available at present: unmodified cellulose (low flux and so-called bio-incompatible membranes), modified/regenerated cellulose (low flux or high flux; so- called relatively biocompatible), synthetic (low flux or high flux; so called relatively biocompatible). The term {u2018}flux{u2019} refers to the permeability of the membrane in the dialyzer across which accumulated toxins and excess fluid pass during hemodialysis. A {u2018}high-flux{u2019} dialyzer has a membrane that allows middle-sized molecules to pass through but prevents the accidental removal of protein from the blood
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: C Levels; Hemodialysis Efficiency; Serum Cystatin